2003
DOI: 10.1590/s0103-84782003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da fidelidade genotípica por marcadores RAPDs de brotações de pereira (Pyrus communis L.) cv. Carrick, regeneradas in vitro

Abstract: O objetivo deste trabalho foi avaliar a fidelidade genotípica de brotações de pereira (Pyrus communis L.) cultivar Carrick, regeneradas in vitro, utilizando marcadores RAPDs. O DNA genômico foi extraído de folhas oriundas das brotações de pereira regeneradas a partir de diferentes tratamentos e de plantas matrizes micropropagadas (planta controle), utilizando-se o protocolo descrito por FERREIRA & GRATTAPAGLIA (1996). Para triagem dos primers foram utilizados os kits OPAN, OPA e OPF (Operon Technologies, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(6 reference statements)
2
0
0
Order By: Relevance
“…Similar results were observed in pear by Erig and Schuch (2003). This result can be explained by the fact that the experimental material originated from explant tissues, in other words, via direct regeneration.…”
Section: Resultssupporting
confidence: 85%
“…Similar results were observed in pear by Erig and Schuch (2003). This result can be explained by the fact that the experimental material originated from explant tissues, in other words, via direct regeneration.…”
Section: Resultssupporting
confidence: 85%
“…The polymorphism was not occurred in regenerated shoots from axillary buds, apical meristem, and leaf whorl disk during the analysis. Erig and Schuch (2003) and Hsie et al (2015) observed similar results in sugarcane and showed 100% true-to-type plantlets. The present results enlighten the fact that plants developed from direct organogenesis are highly stable than those obtained from indirect oraganogenesis (callus) (Kamenickà and Rypák, 1989).…”
Section: Resultssupporting
confidence: 61%